Вплив системи охорони здоров'я на формування людського капіталу у транспортній сфері - Корнілова, Олеся Володимирівна; Корнілова, О. В.; Kornilova, Olesia V.; Кузнецова, Людмила Валентинівна; Кузнецова, Л. В.; Kuznetsova, Liudmyla V. (Одеса : ОНМУ, 2023)
У статті доведено, що прогрес нації найбільше визначається розвитком її людського капіталу, який є головним фактором національного багатства, головним рушійним механізмом соціального прогресу і ключовим показником рівня розвитку суспільства. Визначено, що система охорони здоров’я має значний вплив на формування людського потенціалу транспортної сфери. Доведено, що задля того аби підтримувати та покращувати здоров'я працівників транспортної сфери, система охорони здоров'я має забезпечувати доступ до медичних послуг, проводити профілактичні заходи та надавати психологічну підтримку. У статті зазначено необхідність запровадження та розвитку інноваційних технологій (телемедицина, електронні медичні записи, мобільні додатки та застосування віртуальної реальності). Це дозволяє працівникам транспортної сфери швидко отримати консультацію, діагностику та лікування, а також знижує час очікування та сприяє підвищенню ефективності надання медичної допомоги. Доведено необхідність забезпечення належним обладнанням працівників транспортної сфери. Також зазначено, що постійно треба підвищувати кваліфікацію медичних працівників, які працюють у цій системі. Вони повинні бути ознайомлені з правилами безпеки та впроваджувати новаторські методи лікування та реабілітації, щоб забезпечити найвищий рівень медичної допомоги.

The article proves that the progress of a nation is mostly determined by the development of its human capital, which is the main factor of national wealth, the main driving mechanism of social progress and a key indicator of the level of development of society. It was determined that the health care system has a significant impact on the formation of human potential in the transport sector. It has been proven that in order to maintain and improve the health of transport employees, the health care system must provide access to medical services, carry out preventive measures and provide psychological support. The article states the need for the introduction and development of innovative technologies (telemedicine, electronic medical records, mobile applications and the use of virtual reality). This allows transport employees to receive consultation, diagnosis and treatment quickly, as well as reduces waiting time and improves the efficiency of medical care. It was determined that the health of transport employees has great importance for occupational safety. Productive and safe work requires physical and psychological readiness. It is noted that the health care system helps to identify and eliminate threats to the health of employees, reduce the risks of accidents and injuries during work. This contributes to the creation of safe working conditions and increases the overall level of safety in the transport industry. It has been proven that an insufficient level of development of the health care system can lead to growth in the risk of injuries and accidents at the workplace, which can have serious consequences for both employees and passengers and goods being transported. The need to provide transport employees with proper equipment has been proven. It is also stated that it is necessary to constantly improve the qualifications of medical employees working in this system. They must be familiar with safety regulations and implement innovative methods of treatment and rehabilitation to provide the highest level of medical care.
Корнілова О. В. Вплив системи охорони здоров'я на формування людського капіталу у транспортній сфері / О. В. Корнілова, Л. В. Кузнецова // Розвиток методів управління та господарювання на транспорті : зб. наук. праць. / Одес. нац. мор. ун-т ; редкол.: І. В. Савельєва (голов. ред.) [та ін.]. - № 3 (84). – Одеса : ОНМУ, 2023. – С. 28-39.
Keywords: людський потенціал; формування людського капіталу; система охорони здоров’я; транспортна сфера; human potential; formation of human capital; health care system; transport sector; Research Subject Categories::SOCIAL SCIENCES